Аналіз особливостей роботи надпровідного індуктивного обмежувача струму з додатковим надпровідним екраном (Електротехніка і електромеханіка, 2017)
Проведено аналіз режимів роботи та конструктивної схеми надпровідного обмежувача струму короткого замикання індуктивного типу з додатковим надпровідним екраном. Проведено математичне моделювання магнітної системи обмежувача струму методом скінченних елементів у програмному середовищі FEMM. Проведено розрахунок розподілу магнітних полів у різних режимах спрацювання обмежувача струму короткого замикання на ділянці між основним і додатковим екранами, що дозволяє визначити параметри обмежувача струму Проведен анализ режимов работы и конструктивной схемы сверхпроводящего ограничителя тока короткого замыкания индуктивного типа с дополнительным сверхпроводящим экраном. Проведено математическое моделирование магнитной системы ограничителя тока методом конечных элементов в программной среде FEMM. Проведен расчет распределения магнитных полей в различных режимах срабатывания ограничителя тока короткого замыкания на участке между основным и дополнительным экранами, что позволяет определить параметры ограничителя тока. Purpose. The inductances of magnetic system of a current limiter for the nominal operating mode were determined. The aspects of functioning and a design of a superconducting short-circuit current limiter of inductive type with a superconductive main and additional screens, and superconductive winding, which are placed in a general cryostat on a ferromagnetic core, which ensures an improvement of magnetic field dissipation and in energy efficiency are observed. Methodology. The analysis of distribution of magnetic field of the short-circuit current limiter of inductive type with superconducting high-temperature coil and superconducting main and additional screens, using mathematical modeling by the finite element method in math software package FEMM for different modes of operation is carried out. Results. The calculations of magnetic field dissipation in operational modes are carried out. Originality. The investigations aimed to analyze the influence of distribution of the magnetic field in inductive shortcircuit current limiter with superconducting additional screen on its operation modes. First calculation of the distribution of magnetic fields in different modes of operation for the shortcircuit current limiter in the area between high-temperature superconducting screens. Practical value. The advantage of additional screen of superconducting short-circuit current limiter is to improve screening from dissipation of the magnetic fields of the magnetic system and reducing the power losses at nominal mode. Using the proposed methodology will identify options acceptable to the current limiter mode of operation